Validation of the International Trauma Interview (ITI) among treatment-seeking people with adverse childhood experiences in South Korea - Hyunjung Choi; Hae Seong Lee; Neil P. Roberts (European Journal of Psychotraumatology)
Background: The International Trauma Interview (ITI) is a clinician-administered assessment that has been newly developed for the International Classification of Diseases (ICD-11) diagnoses of posttraumatic stress disorder (PTSD) and complex PTSD (CPTSD).Objective: The current study evaluated the psychometric properties of the ITI for treatment-seeking people with adverse childhood experiences (ACE) in South Korea, with the aims of verifying the validity and reliability of ITI as well as examining the differentiation of ICD-11 CPTSD and borderline personality disorder (BPD).Methods: In total, data of 103 people were analysed. Clinical psychologists conducted the ITI and the structured interview for BPD. Along with the International Trauma Questionnaire (ITQ), self-report measurements on ACE, adulthood trauma, emotion dysregulation, dissociation, depression, adult attachment, BPD symptoms, self-harm, self-compassion, and quality of life were collected. A confirmatory factor analysis (CFA) was conducted to examine the factorial validity and a structural equation model (SEM) was used to evaluate the convergent and discriminant validity.Results: The CFA supported the second-order two-factor model of ICD-11 CPTSD. However, we determined that the alternatively suggested second-order two-factor model of reexperience avoidance combined PTSD and DSO described the data the best. As was hypothesized, ITI PTSD and DSO showed convergent and discriminant validity, and ITI DSO also showed distinctive features with BPD. Interrater reliability and composite reliability were both found to be acceptable. Agreement and consistency between ITQ and ITI were also fair although tentative.Conclusions: The ITI is determined to be a valid and reliable method for the assessment and diagnosis of ICD-11 PTSD and CPTSD, and it is considered to be promising for the differential diagnosis of BPD in South Korean treatment-seeking people with ACE. Future research should aim to assess the agreement between ITI and ITQ while also seeking alternative criteria for ITI PTSD across variant trauma memory features.